2019
DOI: 10.1111/febs.15125
|View full text |Cite
|
Sign up to set email alerts
|

DRG2 supports the growth of primary tumors and metastases of melanoma by enhancing VEGF‐A expression

Abstract: Malignant metastatic melanoma (MM) is the most lethal of all skin cancers, but detailed mechanisms for regulation of melanoma metastasis are not fully understood. Here, we demonstrated that developmentally regulated GTP-binding protein 2 (DRG2) is required for the growth of primary tumors and for metastasis. DRG2 expression was significantly increased in MM compared with primary melanoma (PM) and dysplastic nevi. A correlation between DRG2 expression and poor disease-specific survival in melanoma patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…In the present study, the level of DRG2 expression differed in each prostate cancer cell line, being highest in LNCaP cells and lowest in DU145 cells. These results contradict those of a previously reported study on melanoma [ 20 ]. That study reported that VEGF-A expression was enhanced by DRG2 expression, thus promoting tumor growth and metastasis.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In the present study, the level of DRG2 expression differed in each prostate cancer cell line, being highest in LNCaP cells and lowest in DU145 cells. These results contradict those of a previously reported study on melanoma [ 20 ]. That study reported that VEGF-A expression was enhanced by DRG2 expression, thus promoting tumor growth and metastasis.…”
Section: Discussioncontrasting
confidence: 94%
“…In particular, DRG2 is reported to be involved in G2/M progression, and thus seems to play an important role in the cell response to genotoxic stress. The roles of DRG2 in T cell leukemia, cervical cancer, melanoma, lung cancer, and hepatocellular carcinoma have been reported, but there has been no such study on urological cancers [ 15 16 17 18 19 20 21 ]. Moreover, it is necessary to confirm the association between DRG2 and prostate cancer, which is treated with the chemotherapeutic agent docetaxel, an antimicrotubule agent.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there were several genes identified that were significantly under-expressed in IDH1-mutant astrocytoma compared to IDH1-wildtype. DRG2, developmentally regulated GTP-binding protein 2, has been shown to promote tumor growth and metastasis [ 120 , 121 , 122 ]. Depletion or inhibition of DRG2 was shown to promote survival in mice [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…DRG2, developmentally regulated GTP-binding protein 2, has been shown to promote tumor growth and metastasis [ 120 , 121 , 122 ]. Depletion or inhibition of DRG2 was shown to promote survival in mice [ 122 ]. TRIP4, which is a thyroid hormone receptor interactor, also promotes cell proliferation and migration.…”
Section: Resultsmentioning
confidence: 99%
“…VEGF-A is an essential angiogenic growth factor that is a powerful promoter of the adhesion and proliferation of vascular endothelial cells (44,45). Hence, VEGF-A can regulate the development of various cancers including liver cancer, colorectal cancer, melanoma and lung cancer (46)(47)(48)(49). MiR-126 can inhibit the expression of sprouty-related EVH1 domain-containing gene 1 (SPRED), an inhibiting factor of the MAP kinase (MAPK) pathway, and the p3kr2 (PI3KR2/p85-b) gene, a subunit of PI3K (50-52).…”
Section: Mir-126 and Lung Cancer Tumorigenesismentioning
confidence: 99%